Transforming masculine norms to improve men’s contraceptive acceptance: results from a pilot intervention with men in western Kenya - Sara J. Newmann; Jennifer Monroe Zakaras; Corinne H. Rocca; Phillip Gorrindo; Louisa Ndunyu; Serah Gitome; Mellissa Withers; Elizabeth A. Bukusi; Shari L. Dworkin (Sexual and Reproductive Health Matters, 2023)
Men’s adherence to constraining male gender norms can lead them to resist contraceptive use. Very few interventions have attempted to transform masculine norms to encourage greater contraceptive acceptance and gender equality. We designed and evaluated a small-scale community-based intervention targeting the masculine norms tied to contraceptive resistance among partnered men (N = 150) in two western Kenya communities (intervention vs. control). Pre–post survey data fit to linear and logistic regression models evaluated differences in post-intervention outcomes, accounting for pre-intervention differences. Intervention participation was associated with increases in contraceptive acceptance scores (adjusted coefficient (aβ) 1.04; 95% confidence interval (CI) 0.16, 1.91; p = 0.02) and contraceptive knowledge scores (aβ 0.22; 95% CI 0.13, 0.31; p < 0.001) and with contraceptive discussions with one’s partner (adjusted Odds Ratio (aOR) 3.96; 95% CI 1.21, 12.94; p = 0.02) and with others (aOR 6.13; 95% CI 2.39, 15.73; p < 0.001). The intervention was not associated with contraceptive behavioural intention or use. Our findings demonstrate the promise of a masculinity-driven intervention on increasing men’s contraceptive acceptance and positive contraceptive involvement. A larger randomised trial is needed to test the effectiveness of the intervention among men as well as among couples.